Charitable asymmetric bidders - Olivier Bos (Journal of Public Economic Theory, 2019)
Recent papers show that the all-pay auction is better at raising money for charity than the first-price auction with symmetric bidders under incomplete information. Yet, this result is lost with sufficiently asymmetric bidders under complete information. In this paper, we consider a framework on charity auctions with asymmetric bidders under some incomplete information. We find that the all-pay auction still raises more money than the first-price auction. Thus, the all-pay auction should be seriously considered when one wants to organize a charity auction.
Keywords: 330